Criteria for Success: A study of primary technology teachers' assessment of digital portfolios - Hartell, Eva; Skogh, Inga-Britt (Australasian Journal of Technology Education, 2015)
Transparency regarding criteria for success in assessment processes is challenging for most teachers. The context of this study is primary school technology education. With the purpose to establish what criteria for success teachers put forward during the act of assessment, think-aloud protocols were collected from five primary teachers during an assessment act. Results are based on content analysis of think-aloud protocols and quantitative measures of reliability in order to ascertain teachers’ motives for decision-making when assessing Year 5 pupils’ multimodal e-portfolios. Findings show consensus among these teachers, focusing on the execution of the task in relation to the whole, rather than to particular pieces of student work. The results confirm the importance of task design, where active learning in combination with active tutoring is an integral part, including provision of time and space for pupils to finish their work.